Synthesis, Characterization and Optimization of Carbon Micro-Nano Filler and its Bio-composites - Perry Law, Nyuk Khui (UNIVERSITY OF MALAYSIA SARAWAK, 2022)
Synthesized carbon (biochar) from microwave assisted pyrolysis Jatropha seeds demonstrate great potential as bio-filler for bio-composite development. However, no research has been done so far on the pyrolysed Jatropha seed using ball milling approach for the biochar fabrication and develop bio-composite for engineering applications including biomedical. Therefore, the main aim of this research is to synthesis and characterize microwave-pyrolysis biochar using ball milling approach to develop micro-nano bio-filler reinforced poly lactic acid (PLA) bio-composites. After 30 hours of ball milling, the biochar manages to reduce into micro-nano size range. The Scanning Electron Microscopy (SEM) show Jatropha seed biochar reduced from macro-size to micro-nano range 10 µm - 600 nm. Energy Dispersive X-ray Spectroscopy (EDS) results indicated an increase in carbon mass percentage from 72.6% to 81.2%, while the Brunauer-Emmett-Teller (BET) analysis showed an increased in surface area from 0.10 m2/g to 3.67 m2/g after 30 hours of ball milling. Fourier Transform Infrared Spectroscopy (FTIR) showed an increase in the percentage of transmittance after ball milling the biochar for 30 hours, with a reduction of moisture (alcohol, phenol, and water). The developed bio-composites are PLA/BC, which is PLA and bio-filler only, and PLA/PEMA/BC which is with the added compatibilizer Poly (Ethylene-Alt-Maleic Anhydride) (PEMA). Percentage of weightage for all materials for bio-composite fabrication are based on the D-optimal model design via StatEase Design Expert software. D-optimal mixture design models help to predict the mechanical properties of the bio-composites, as according to the response input (Mechanical Tensile and Microhardness Test Result). Noise level of the model dictates the accuracy and reliability to obtain the predicted values. Predicted optimum mixture content is found to be around PLA/BC 2wt% and PLA/PEMA/BC 1.25wt%. The developed bio-composites showed that higher bio-filler content increases the microhardness. However, the tensile strength and modulus of elasticity did not improve with higher bio-filler content, due to the brittle nature of the bio-composite structure, which could be observed in the SEM results. FTIR results for PLA/BC bio-composites were similar to PLA/PEMA/BC. Bio-composites with lower bio-filler content showed peak intensities which were more pronounced than higher bio-filler content. This correlated to the performance of the tensile strength and optimum bio-filler content. The additional PEMA in PLA/PEMA/BC showed peaks that were more pronounced, which showed the interaction between bio-filler and matrix to be better, hence affecting the mechanical performance. Overall, the introduction of bio-filler did not have much alteration in functional groups. Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) analysis demonstrated that the developed bio-composites had slightly better thermal stability compared their neat control samples. The improve thermal stability of PLA/PEMA/BC was attributed to the additional hydroxyl group by the introduction of PEMA, which improved interaction between bio-filler and polymer matrix.